Proposta de ensino de dilatação térmica linear utilizando simulação - Oliveira, Danilo Augusto Araújo (2023)
This monograph aims to present a proposal for teaching thermal expansion, using a simulation as an educational tool. Thermal expansion is a physical phenomenon present in people's daily lives, but it is often a difficult topic for students to understand, due to its subtle nature and difficult perception in everyday life. In this study, a literature review was carried out on the concept of thermal expansion, exploring its theoretical bases and practical applications. Furthermore, the challenges encountered by teachers when approaching this topic in the classroom and the possible existing pedagogical solutions were analyzed. The teaching proposal presented in this monograph is based on the use of a computer simulation as a complementary strategy to traditional teaching. The simulation allows students to interactively and dynamically visualize the behavior of materials when they are heated or cooled, facilitating the understanding of the concepts of thermal expansion. To validate the proposal, an exploratory study was carried out with a group of students who took the Experimental Physics Laboratory for Engineering subject, where real practical activities were applied after social isolation and involving simulation during the period of this social isolation. In short, the proposal for teaching linear thermal expansion using the simulation presented in this monograph proves to be a promising approach to improving student learning on this topic. The integration of simulation into the school curriculum can contribute to making teaching more meaningful, arousing students' interest and facilitating the understanding of the physical phenomena involved in thermal expansion.